Lactose esters: synthesis and biotechnological applications. (17th February 2018) - Staroń, Jakub; Dąbrowski, Janusz M.; Cichoń, Ewelina; Guzik, Maciej
Abstract: Biodegradable nonionic sugar esters-based surfactants have been gaining more and more attention in recent years due to their chemical plasticity that enables the various applications of these molecules. In this review, various synthesis methods and biotechnological implications of lactose esters (LEs) uses are considered. Several chemical and enzymatic approaches are described for the synthesis of LEs, together with their applications, i.e. function in detergents formulation and as additives that not only stabilize food products but also protect food from undesired microbial contamination. Further, this article discusses medical applications of LEs in cancer treatment, especially their uses as biosensors, halogenated anticancer drugs, and photosensitizing agents for photodynamic therapy of cancer and photodynamic inactivation of microorganisms.